An organic–inorganic solid–electrolyte interface generated from dichloroisocyanurate electrolyte additive for a stable Zn metal anode in aqueous Zn batteries. Issue 34 (6th April 2023) - Liu, Fangming; Wang, Kuo; Li, Qianrui; Zhang, Guoli; Zhu, Jiaqi; Liu, Xiao-Xia; Sun, Xiaoqi
Abstract : A dichloroisocyanurate additive is introduced to the ZnSO4 electrolyte for aqueous zinc batteries. It generates an organic–inorganic solid–electrolyte interface on the Zn electrode and enhances the cycling stability. Abstract : Dendrite growth and side reactions of the Zn metal anode limit the cycle life of aqueous Zn batteries. Herein, we propose a sodium dichloroisocyanurate electrolyte additive with a low concentration of 0.1 M to modify the Zn interface environment and construct a stable organic–inorganic solid–electrolyte interface on the Zn electrode. It suppresses corrosion reactions and directs uniform Zn deposition. The cycle life of the Zn electrode in symmetric cells extends to 1100 h at 2 mA cm −2 and 2 mA h cm −2, and the Zn plating/stripping coulombic efficiency reaches 99.5% for more than 450 cycles.